Evaluating the Performance of Zakat Institutions in Empowering Mustahiq Using Islamic Performance Index Model: A Case Study of Dompet Dhuafa North Sumatra Indonesia - Aslami, Nuri; Albani Nasution, Muhammad Syukri; Lubis, Fauzi Arif; Chanda Chansa Thelma (Journal of Islamic Economic and Business Research, 2025)
This study aims to describe and explain the measurement of LAZ performance in the transformation of entitled to receive Zakat empowerment using the Islamic Performance Index (IPI) model at the Amil Zakat Institution Dompet Dhuafa North Sumatra. This type of research is field research using a comparative descriptive method with a quantitative approach. The research population was 1838, and they were entitled to receive Zakat in 2022. The sample used was 329 Entitled to Receive Zakat. The analysis technique used in this research is the Islamic Performance Index (IPI), which is the indicator used to determine the condition of entitled-to-receive Zakat households. The results of this study indicate that the IPI model can be used to measure amil Zakat institutions' performance in empowering entitled to receive Zakat welfare. Even so, in this study, the increase in material income is not very significant. This happens because the entitled to receive Zakat used as a sample of respondents are consumptive beneficiaries or ZIS, so it does not significantly increase the entitled to receive Zakat income at LAZ Dompet Dhuafa Waspada. In comparison, the increase in the number of people entitled to receive Zakat religiosity looks very significant after receiving Zakat, infaq, and sadaqah.